Influence of inorganic scintillator light output non-proportionality and energy of registered ionizing radiation on radiometric parameters of detectors on their base - Viday, Yu.T.; Tarasov, V.A.; Gorbacheva, T.E. (Functional Materials, 2008)
The effect of the non-proportionality in light yield and the radiation energy on the radiometric characteristics of thallium-doped cesium iodide detectors and p-terphenyl ones. The increase of the non-proportionality in the energy and light yield at the recording of 5 MeV and 2 MeV a-particles has been shown to result in an increased background counting rate, decreased detector sensitivity and resolution. These changes in radiometric parameters are influenced significantly by the state of the radiation input surfaces of the Csl(TI) and p-terphenyl detectors.